Physical Activity for Health and Fitness in Female Undergraduate Students - Bosnar, Ksenija; Gošnik Oreb, Jelka (2000)
The sample of 321 female undergraduate students of The Faculty of Phylosophy of University of Zagreb, participating in regular exercise programs at the university, were measured by SITA scale (Horga, Baršnik, 1991) developed to measure attitudes explaining reasons for exercising. Scale consists of eight subscales, six of them based on Kenyon's theoretical model (1968) - Physical activity for health and fitness, as a social experience, as the pursuit of vertigo, as an aesthetic experience, as catharsis, and physical activity as an ascetic experience, and two additional subscales - physical activity as play, and physical activity as need for movement. The results of research show that the main motive for exercising was improving health and fitness, followed by aesthetic experience. Lowest in rank is the pursuit of vertigo and ascetic experience. The analysis of matrix of scale correlation coefficients shows that scales form highly homogeneous system. The common variance of health and fitness motive with others show that health motive is not independent inside complex structure of exercise motives, but is specific enoug to be treated and studied separately.
Projekt MZOS
ENG